ANALYSIS OF MATHEMATICAL REFLECTIVE THINKING ABILITY IN THE MATERIAL OF ALGEBRA BASED ON GENDER - Hikmafadlia, Isti; Utami, Nida Sri (Jurnal Pendidikan Matematika dan IPA, 2025)
Reflective thinking comprising Techniques, Monitoring, Insight, and Conceptualization stages, plays a crucial role in students"™ problem-solving skills in mathematics. This study aims to analyze and describe the reflective thinking abilities of students in algebra, based on gender differences. This is a descriptive research using a qualitative approach, which involves students with varying levels of mathematical thinking ability. The students include a male student with a high mathematical thinking ability (SLT), a male student with a medium mathematical thinking ability (SLS), a male student with a low mathematical thinking ability (SLR), a female student with a high mathematical thinking ability (SPT), a female student with a medium mathematical thinking ability (SPS), a female student with a low mathematical thinking ability (SPR). The study showed that there are some similarities and differences between male and female student in their reflective thinking ability. Generally, male students have a better reflective thinking ability than female students.